Endodontic management of an infected geminated primary incisor-A case report - Rao, Dinesh (Journal of Case Reports in Dental Medicine, 2025)
The formation of human dentition is a highly intricate process. Any disruptions during the various stages of tooth development can lead to distinct abnormalities, affecting either the primary or permanent teeth. Gemination and fusion are dental anomalies that affect tooth morphology, resulting in the appearance of an unusually wide tooth. Fusion and gemination are often referred to using terms such as double teeth, double formation, conjoined teeth, geminifusion, vicinifusion, and dental twinning. Double teeth can lead to various clinical issues, including aesthetic concerns, spacing irregularities, and an increased risk of tooth decay. Effective management of these cases requires a thorough understanding of the condition and its associated complications. This report presents a case of a 2-year-old boy with a primary maxillary left central incisor presenting a double tooth. The tooth was carious and pulpally involved. The condition was managed conservatively through endodontic treatment, followed by aesthetic rehabilitation using direct composite restoration. Regular clinical and radiographic evaluations were conducted every three months. No abnormalities were observed during these follow-up visits. Managing PDT may involve a multidisciplinary approach, and early diagnosis is essential to prevent and address potential complications in both primary teeth and their permanent successors.